RE-CLOSED BORDER AS AN EVERYDAY EXPERIENCE. EXPLORATORY RESEARCH OF POLISH-GERMAN TWIN CITIES IN THE FIRST MONTHS OF A COVID-19 PANDEMIC - FRĄCKOWIAK, MACIEJ; KACZMAREK, JERZY; ROGOWSKI, ŁUKASZ (Society Register, 2021)
Borders’ closure during the COVID-19 pandemic had a particular impact on the everyday life of borderland residents. As part of the research on bordering processes carried out since a few years, during the closure of the state borders in 2020, qualitative interviews on everyday life in the COVID-19 pandemic have been conducted. In this paper, we present the results of the exploratory study on the impact of the COVID-19 pandemic on Polish-German border twin cities. We indicate at what levels borders’ closure affected the border landscape, border practices of the inhabitants of the researched territories, and their notion of the border. We also suggest how border relations were shaped due to differences in the management and perception of the pandemic situation in two countries. The results obtained indicate that the closure of borders has made life more difficult in an area under examination and has also affected the identity and specificity of the place. This issue is worth exploring further to establish the true extent of the impact of the pandemic in the borderlands.